Recent experience with comprehensive civil and military approaches in international operations - Julien Brett (Danish Institute for International Studies (DIIS), 2009)
This report provides a rapid mapping analysis of the existing documentation concerning civil and military approaches in international operations. Its main purpose is to extract and review key lessons learned and dilemmas from recent experiences in Afghanistan, Iraq and other international operations where foreign military forces are, or have been, participating in a process of political and security stabilization.
Keywords: 300; Internationale Truppe; Militär; Gesellschaft; Friedenssicherung; Welt